THE EFFECT OF EMPLOYMENT CONFLICT, JOB STRESS AND WORK OVERLOAD ON JOB SATISFACTION OF FINANCIAL MANAGEMENT AGENCY EMPLOYEES AND REGIONAL REVENUE OF KOTA PARIAMAN - Suhelmi Helia; Herni Pratiwi; Claudia Ivonne; Aldi Riswanto (SEAN Institute, 2022)
This study aims to see the effect of (1) work conflict on employee job satisfaction Pariaman City BPKPD, (2) job stress on employee job satisfaction Pariaman City BPKPD, (3) work overload on employee job satisfaction Pariaman City BPKPD, (4) work conflict, job stress and work overload simultantly on employee satisfactionPariaman City BPKPD. The population in this study are 60 employees at BPKPD Pariaman City. The sampling technique uses a total sampling technique (whole sample), total sampling is a sampling technique where the number of samples is the same as the population. The results of this study indicate that (1) work conflict has a significant negative effect on employee job satisfaction at BPKPD Pariaman City, (2) job stress has a significant negative effect on employee job satisfaction at BPKPD Pariaman City, (3) work overload gives a significant negative effect on employee job satisfaction at BPKPD Pariaman City, and (4) work conflict, job stress and work overload together have a significant effect on employee job satisfaction at BPKPD Pariaman City.